Plasma lens for MeV heavy ion beam focusing - Il’enko, B.P.; Nekludov, I.M.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2000)
The investigations of heavy ion beam focusing and governing that were carried out at the accelerator of heavy ions «UTI-1». are represented. The focusing of continuous ion beam of Mo⁺⁴ (0.9 MeV, 25 mA) by plasma lens (PL) was investigated. PL was produced by ion beam itself due to ionization processes at hydrogen leak-in (0.5— 1 cm³/min) and confinement of electrons by applyed magnetic field of intensity 0.8 kOe. Beam focusing was estimated from measuring of beam diameter decreasing and corresponding current density increasing.